Airway function tests and vocal cord paralysis in lung transplant recipients - Zapletal, Alois; Kurland G; Boas SR; Noyes BE; Greally P; Faro A; Armitage JM; Orenstein DM (Pediatric pulmonology, 1997)
Maximum expiratory and inspiratory flow-volume (MEFV, MIFV) curves, specific airway conductance (sGaw), and flexible fiberoptic laryngoscopy were examined in 8 pediatric lung transplant recipients with vocal cord paralysis (VCP). Six were heart-lung (H-L) and 2 double-lung (D-L) recipients, 7 had left VCP, and 1 had right VCP. Based on the pulmonary function tests (PFT), 2 subgroups could be distinguished in the 8 recipients with VCP. Group A (5/8 recipients; mean age, 13 +/- 3.4 years; mean height, 144.3 +/- 12.3 cm) had significantly reduced specific airway conductance (sGaw; < 2 SD from predicted) and normal MEF25, MEF50, peak expiratory flow (PEF), forced expiratory volume in 1 second (FEV1), and %FEV1/forced vital capacity (FVC); this pattern suggested variable extrathoracic airway obstruction. PIF was normal in 4/5 and reduced in 1/5 of these recipients. Group B (3/8 recipients with VCP; mean age, 17 +/- 2.4 years; mean height, 156.3 +/- 12.0 cm) had significantly reduced sGaw, MEF25, MEF50, PEF, FEV1, and %FEV1/FVC, implying primarily small airway obstruction. These recipients had bronchiolitis obliterans. The results suggest that a pattern of reduced sGaw and normal MEFs, PEF, FEV1, and PIF should raise the possibility of VCP in patients after lung transplantation. sGaw is more sensitive than PIF and PEF in identifying airway obstruction due to VCP, and should be routinely included in the follow-up evaluation of lung transplant recipients.
Keywords: Female; ochrnutí hlasivek; Pulmonary Ventilation; respirační funkční testy; Adolescent; Vocal Cord Paralysis; mužské pohlaví; transplantace plic; Humans; usilovný výdechový objem; Postoperative Complications; Lung Transplantation; lidé; Forced Expiratory Volume; Respiratory Function Tests; laryngoskopie; ženské pohlaví; Child; plicní ventilace; pooperační komplikace; dítě; Laryngoscopy; Male; mladiství